2019
DOI: 10.1186/s13104-019-4810-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality-based cognitive training in older adults living without and with mild dementia: a pretest–posttest design pilot study

Abstract: ObjectiveModern technologies are increasingly used in the development of cognitive interventions for older adults. Research into possible applications of virtual reality in such interventions has begun only recently. The aim of present study was to evaluate the effects of 8 sessions of VR-based cognitive training using the GRADYS game in healthy older adults (n = 72; aged 60–88) and older adults living with mild dementia (n = 27; aged 60–89).ResultsOlder adults with mild dementia demonstrated worse baseline co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 46 publications
1
37
0
5
Order By: Relevance
“…Recently, with the advancement of IT technology, virtual reality-based cognitive rehabilitation (VRCR) has been proposed [14,15]. VR facilitates the creation of a multisensory, dynamic, interactive virtual environment with a great similarity to real life [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the advancement of IT technology, virtual reality-based cognitive rehabilitation (VRCR) has been proposed [14,15]. VR facilitates the creation of a multisensory, dynamic, interactive virtual environment with a great similarity to real life [16].…”
Section: Introductionmentioning
confidence: 99%
“…With rapid developments in virtual reality (VR) technology, there has been a growing interest in adopting VR in cognitive interventions over the years. However, as previous research concerning VR has mainly focused on the diagnosis of dementia, there are only a handful of studies on the effects of VR‐based cognitive interventions 20,21 . According to the most recent meta‐analysis by Kim et al ., VR interventions showed small to medium effects on cognition, larger in patients with MCI than in those with dementia 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancement and enhanced education level of aging population demand more effective and evidence-based cognitive trainings. Besides conventional computer-based cognitive training (CBCT), immersive virtual reality cognitive training (VRCT) has been gaining popularity over the last decade [6]. Previous studies have suggested that implementation of CBCT and VRCT among individuals with MCI may lower the risk for developing Alzheimer's disease and related dementia [5,7].…”
Section: Introductionmentioning
confidence: 99%